Prostate Specific Antigen (PSA) testing practices in an academic healthcare organization - Margarita Echeverri; Elizabeth Yanes; David Anderson; Anna María Nápoles (Journal of Men's Health, 2022)
Background: It is estimated that one out of nine men will be diagnosed with prostate cancer in their lives. However, there is so much debate about the impact of guidelines in prostate specific antigen (PSA) screening for early detection of prostate cancer. Although some studies have examined variation in PSA-based screening for prostate cancer, they have not considered the impact that the type of health insurance and clinician specialty may have in PSA-screening practices. Methods: Retrospective medical chart review of 500 male patients (40–69 years old). ANOVAS and logistic regression tested for significant differences in the variables of interest. Results: The majority (83%) of patients did not receive any type of PSA-testing during the study period. Patients of older age and those having private insurance were more likely to have a PSA-test. Of those patients who had PSA testing (n = 83), half received it for prostate cancer screening. The majority of the PSA-tests performed (n = 214) were ordered by urologists, received by White patients, and covered by private insurance. Conclusions: In this study, type of health insurance and age were associated with receipt of a PSA test, as opposed to race. Considering that male patients usually go to the urologists only when they have prostate symptoms, primary care clinicians may benefit from continued education on counseling patients, especially those who may be at elevated risk, regarding the importance of prostate health and PSA exams in general.